School health program and the alignment of actions in the prevention of coronavirus (Research, Society and Development, 2021)
The Health and Prevention in Schools Program was designed and implemented by the Ministry and aims to guarantee the approach to specific health topics. Currently, in addition to the 12 actions already recommended, actions on “Health promotion and prevention to COVID-19” have been included. The objective of this study was to understand how the actions of the School Health Program are carried out in the prevention of coronavirus. This is a qualitative research carried out in July 2020. Teachers from a basic education school in the Western Frontier of Rio Grande do Sul participated in the research. Data collection was performed using an online form. The survey was approved under registration number 3,704,100. 17 teachers participated, among which 15 are female and two male. Regarding the articulation between health and schools in the territory, the teachers said that the development of 12 actions or more is recommended. During the pandemic period, teachers changed the focus of the program's actions and addressed issues related to Covid-19, and teachers are also preparing materials with Coronavirus Prevention tips and tips to make the quarantine lighter and healthier. From the analyzes raised, we realized that the Covid-19 Pandemic transformed the pedagogical methodology of the schools, mainly of the school that was the object of research, since Remote Education enabled a continuity in the integration with the activities developed by the Program.